2023
DOI: 10.1186/s12974-023-02740-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diabetes on microglial physiology: a systematic review of in vitro, preclinical and clinical studies

Abstract: Diabetes mellitus is a heterogeneous chronic metabolic disorder characterized by the presence of hyperglycemia, commonly preceded by a prediabetic state. The excess of blood glucose can damage multiple organs, including the brain. In fact, cognitive decline and dementia are increasingly being recognized as important comorbidities of diabetes. Despite the largely consistent link between diabetes and dementia, the underlying causes of neurodegeneration in diabetic patients remain to be elucidated. A common facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 279 publications
0
13
0
Order By: Relevance
“…Additionally, even metabolic factors, like glucose levels can impact microglial activity. Conditions, such as diabetes or hyperglycemia, can lead to increased microglial reactivity, marked by upregulation of various molecules and pathways associated with glucose transport and sensing and inflammation and oxidative stress ( Hsieh et al, 2019 ; Iannucci et al, 2022 ; Vargas-Soria et al, 2023 ).…”
Section: Microglia Functionmentioning
confidence: 99%
“…Additionally, even metabolic factors, like glucose levels can impact microglial activity. Conditions, such as diabetes or hyperglycemia, can lead to increased microglial reactivity, marked by upregulation of various molecules and pathways associated with glucose transport and sensing and inflammation and oxidative stress ( Hsieh et al, 2019 ; Iannucci et al, 2022 ; Vargas-Soria et al, 2023 ).…”
Section: Microglia Functionmentioning
confidence: 99%
“…Regarding the mechanism for the association between diabetes and AD, a small but relevant study showed that those with MCI who progressed to dementia had a reduced cerebral metabolic rate of glucose metabolism, which is because cerebral insulin resistance is heightened in diabetics [ 18 ]. Additionally, diabetes affects microglial function; a review that examined 267 articles found that diabetes modulates microglia by affecting their secretion of a wide variety of cytokines and chemokines (NF-κB, NLRP3 inflammasome, fractalkine/CX3CR1, MAPKs, and Akt/mTOR), their metabolic reprogramming, and their increased promotion of reactive oxygen species (ROS) [ 19 ]. Brabazon et al showed that insulin reduced the pro-inflammatory M1 microglial phenotype [ 20 ].…”
Section: Diabetes Insulin Resistance and Admentioning
confidence: 99%
“…Amongst these, Van Dyken and Lacoste argued that neuroinflammation is one of the key mechanistic connectors between diabetes and AD [71]. Similarly, based on a systematic review of in vitro, preclinical and clinical studies, Vargas-Soria et al concluded that diabetes triggers specific responses that include the upregulation of activated microglia and secretion of a wide variety of pro-inflammatory cytokines and chemokines [72]. Pathways commonly activated by diabetic pathological changes include the NLRP3 inflammasome.…”
Section: Diabetes Mellitusmentioning
confidence: 99%